Implementasi Peran Guru Bimbingan dan Konseling dalam Perencanaan Karier Siswa Melalui Bimbingan Karier dengan Media Mind Mapping - Dwi Purnama, Ranita; Sugara, Hendry (Jurnal Bimbingan dan Konseling Pandohop, 2025)
Career planning is a crucial aspect of education, especially for high school students who are in the stage of exploring their future. A lack of understanding of self-potential, interests, and career-related information often leads to difficulties in determining career direction, resulting in inappropriate educational choices and increased risk of career failure. This study aims to examine the effectiveness of using the mind mapping method in career guidance services. A literature review approach was employed by analyzing various sources related to the implementation of mind mapping in educational and counseling contexts.The findings indicate that mind mapping enhances students’ career planning skills, helps them focus on setting future goals, and facilitates guidance and counseling teachers in delivering services more creatively and systematically. This technique supports visual and reflective thinking processes, encouraging students to construct meaningful and personalized career paths. In conclusion, mind mapping is an effective medium in career guidance services. It is recommended that this method be systematically integrated into school-based career guidance programs, supported by teacher training to ensure its optimal application.